Bond strength of adhesive restorations to Er : YAG laser-treated dentin - Malta, D. A. M. P.; Kreidler, M. A. M.; Villa, G. E.; de Andrade, M. F.; Fontana, C. R.; Lizarelli, R. F. Z. (Wiley-Blackwell, 2007)
Background and Objective: evaluate the adhesion of adhesive restorations with and without a base of resin-modified glass-ionomer cement (RMGIC) to dentin irradiated with Er:YAG laser.Study Design/Materials and Methods: Twenty-four human molar teeth were divided into 6 groups (n=4): G1) 37% Phosphoric acid (PA) + Adhesive system (Ad) + Composite resin (CR); G2) RMGIC + CR; G3) Laser (60mJ-5Hz-20s) + PA + Ad + CR; G4) Laser (60 mJ-5 Hz-20 s) + RMGIC + CR; G5) Laser (100mJ-5Hz-20s) + PA + Ad + CR; G6) Laser (100mJ-5Hz-20s) + RMGIC + CR. Teeth were prepared, restored and cut into specimens, according to the treatment proposed and to methodology for microtensile test. Data were submitted to ANOVA and Tukey statistical tests (alpha=5%).Results:. The mean values for adhesion (MPa) and standard deviation (+/- SD) were: G1) 26.30(+/- 4.50), G2) 5.34(+/- 2.87), G3) 21.16(+/- 6.01), G4) 5.22(+/- 1.52), G5) 22.23(+/- 4.98), G6) 5.25(+/- 3.08).Conclusion: the use of Er:YAG laser did not influence on the restorations adhesion.
Keywords: adhesion; dentin; Er : YAG laser; micro-tensile bond strength; resin-modified glass-ionomer cement